Developing Simulators for Company Games: Design Approaches - Westphal, Fernando Kaname; Lopes, Paulo da Costa (Revista Gestão da Produção Operações e Sistemas, 2007)
Faced with the visible growth of the use of company games in teaching production engineering and other professional formation areas, the absence of systematized references can become an obstacle to the development of new games and simulators. In this context, the present bibliographical study sought to introduce the key structural elements in developing simulators for company games. Thus, three approaches to simulator design (GOOSEN, 1981; TEACH, 1990; HALL, 2005) are analyzed in general terms, and where four structural elements for developing simulators are highlighted and treated in greater depth: (a) scenarios (GOOSEN, 1981); (b) decisions (KEYS; BIGGS, 1990); (c) algorithm modeling (GOLD; PRAY, 1983; GOOSEN, 1986; TEACH, 1990b; GOLD; PRAY, 2001); and (d) performance evaluation methods of participants in company games (ANDERSON; LAWTON, 1988, 1990). The set of studies summarized and analyzed herein can become an important reference source for new developers of simulators for company games and for those who study the area. Key words: Simulators; Company Games; Simulator Design.